Substitution of Anchovy Waste Flour for Fish Meal as Conventional Feed on Quail Performance (Coturnix-coturnix japonica) - Putra, Andhika; Dahlan, Ismail; Pratama, Andika (Indonesian Journal of Agricultural Research, 2018)
Quail (Coturnix coturnix japonica) is one of the leading poultry that has a pretty good role and prospect as an egg producer and as a meat producer. The most important factor in the maintenance of quail is feed, because 80% of the costs incurred by farmers for the purchase of feed. Attempts to rotate waste is to utilize anchovy Waste enough to be used as a substitution of fish meal in the manufacture of artificial feed quail. Anchovy waste in artificial feed is expected to reduce the use of fish meal in quail feed. From the results of proximate test that has been done the protein content of starch produced 44.43%.The purpose of this research is to know the content of the fish waste flour as a feed conventional to the growth. The method used in this research is Randomized Complete Design (RAL) with 5 treatments and 4 replications. Parameters used were feed consumption, average weight gain and feed conversion. The results showed that the use of anchovy waste flour as conventional feed was very helpful in the consumption of rations, weight gain and feed conversion. The conclusion of this study is used of anchovy waste can replace fish flour as a protein source in laying quail rations.